Letter to Assemblyman John Vasconcellos from Jane Tolmach - Jane Tolmach:::::: (1976)
In a May 7, 1976 letter, Jane Tolmach wrote to Assemblyman John Vasconcellos seeking his support for her campaign for the 36th Assembly District seat in Ventura County. She noted that Ken MacDonald was not seeking reelection and described her campaign's strong early progress, including successful events featuring prominent Democratic figures such as Edmund G. "Pat" Brown, Sr., and Mayor Tom Bradley. Tolmach highlighted her campaign's organization, targeted voter outreach, and endorsements from groups including the California Federation of Teachers, United Auto Workers, Business and Professional Women's clubs, and Women For. She expressed confidence in winning the Democratic-leaning district's primary, citing favorable registration numbers. The letter concluded with a request for any assistance he could provide to her campaign.